ЧИСЛЕННОЕ МОДЕЛИРОВАНИЕ ЭЛЕКТРОМАГНИТНЫХ ПРОЦЕССОВ В СХЕМЕ МАГНИТНОГО ГЕНЕРАТОРА ИМПУЛЬСОВ - Христо , А.И.; Зозулев, В.И.; Шолох , Д.А. (Інститут електродинаміки НАН України, Київ, 2014)
A advanced analysis of the existing models of the switching choke is made. An improved model of the switching choke, which takes into account the non-linearity and the ambiguity of the magnetization characteristic of its core, is offered. Numerical simulation of transient processes in a magnetic pulse generator with a key in the charging circuit is produced. Graphs of electrical and magnetic characteristics of the process are received. The modes of its operation at different load resistances and parameters of the bias circuit are analyzed. References 8, figures 4.